Public Health Training Centers' Support for Community Health Workers: Case Studies of Needs Assessment, Training, and Student Field Placement Initiatives. (September 2022) - Lederer, Alyssa M.; Barrett, Karla Todd; Shorter, Charles; Kenefick, Hope W.; Kulik, Phoebe K. G.; Morales, Marcia; Reinschmidt, Kerstin M.; Shrestha, Sweta
Abstract : Context: Community health workers (CHWs) are vital frontline public health workers. Given their trusted roles and connection to and understanding of the communities they serve, CHWs are able to link underserved communities to resources and public health agencies. With CHWs' increased prominence in the public health workforce, calls have been made for expanding and supporting CHW training and career development opportunities. Program: Public health training centers (PHTCs) are mandated to assess public health workforce needs, provide evidence-based professional development trainings, and increase students' aptitude for working with underserved and underresourced communities through applied practice experiences. Public health training centers can support CHWs in each of these areas. Design: Case studies from 3 PHTCs are provided to exemplify how PHTCs are well positioned to support the critical CHW workforce via assessment, training, and student field placements. Implementation: A regional needs assessment survey with a designated section for CHWs, the provision of accessible and relevant CHW training, and CHW-focused student field placements were implemented in PHTC Regions 6/South Central, 1/New England, and 5/Great Lakes, respectively. Evaluation: The Region 6 needs assessment found that CHWs in Oklahoma had multiple core roles and training interests. A crosswalk of needs and available training in the region guided the creation of tailored CHW trainings. Across 35 CHW-targeted trainings in Region 1, 88.5% of trainees were satisfied with the trainings and identified actions they could take to apply information they learned to their work. Significant improvements ( P < .001) in knowledge occurred across the 13 trainings that had pre-/posttests. In Region 5, students engaged with CHW-based organizations in Wisconsin to inform statewide CHW priority action items and deliverables and found the field placements meaningful for their academic experience. Discussion: Public health training centers' strengths in workforce development can complement and extend existing efforts to support the CHW workforce.